Auguste Comte Dan Ide Positivismenya - Udi Mufrodi Mawardi (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2008)
Sebagai ahli waris zaman renaissance, filsafat zaman modern memang bercorak